Multifunctional potential of triazole-based metal-organic frameworks: An overview - Priya Mishra; Nidhi Singh; Satya; Armeen Siddique; Seema Joshi (Chemistry of Inorganic Materials)
Triazole-based Metal-Organic Frameworks (Tz-MOFs) are a special type of material that combines the triazole ligands with the MOFs. These frameworks are made by linking metal ions or clusters with nitrogen-rich triazole derivatives that can bind in different ways. They work better for storing and separating gases, especially for capturing CO2 and storing hydrogen, because they have a larger surface area and can selectively adsorb. Triazole ligands work well with metal centers, which makes them better at catalyzing reactions. This makes them useful for electrocatalysis, photocatalysis, and organic transformations. These MOFs are good chemical sensors because they can easily and accurately find biomolecules, heavy metals, and toxic gases. Tz-MOF's controlled release property and biocompatibility make them promising for drug delivery in biomedical applications. Their potential in healthcare is further enhanced by their antimicrobial activity. The focus of recent advancements is on improving their operational stability, scalability, and functionalization for practical applications. These materials offer a cutting-edge platform for tackling significant issues in environmental sustainability, medicine, and energy storage. This review presents a comprehensive analysis of Tz-MOFs, emphasizing their structural diversity and applications. These MOFs are ideal for a range of applications due to their structures, adjustable porosity, and excellent thermal stability.